The effect of granulocyte colony‐stimulating factor dose and administration interval after allogeneic hematopoietic cell transplantation on early engraftment of neutrophil and platelet. Issue 12 (21st October 2021) - Noorazar, Leila; Bonakchi, Hossein; Sankanian, Ghazaleh; Parkhideh, Sayeh; Salimi, Maryam; Hajifathali, Abbas; Mirfakhraie, Reza; Roshandel, Elham
Abstract: Background: Hematopoietic stem cell transplantation (HSCT) is one of the treatments for hematologic malignancies. Numerous factors affect the HSCT outcome. The purpose of this study was to investigate the effect of post‐HSCT administration of granulocyte colony‐stimulating factor (post‐G‐CSF) on early neutrophil and platelet engraftment in allogeneic HSCT (allo‐HSCT). Material & methods: The study was performed on 76 patients diagnosed with AML and ALL. All patients underwent allo‐HSCT at Taleghani stem cell transplantation center, Tehran, Iran, from February 2016 to December 2018. Chemotherapy regimens based on patients' conditions were selected between myeloablative and reduced‐intensity regimens. Results: Statistical analysis revealed that the number of administered G‐CSF units after HSCT was a time‐dependent variable. Statistical analysis before day +11 reported that patients who received G‐CSF <14 units had three times better early neutrophil engraftment than those with G‐CSF ≥14 (CI 95%, AHR = 3.03, p :0.002). CD3+ cells count <318.5 × 10 6 /kg was associated with fast platelet engraftment (CI 95%, AHR 2.28, p :0.01). Conclusion: In this study, post‐G‐CSF stimulation was associated with early engraftment in a time‐ and dose‐dependent manner. Administration of G‐CSF beyond 14 units resulted in adverse effects on neutrophil early engraftment. It also appeared that with a reduction in CD3+ cell counts, the likelihood of GVHD decreases, and platelet engraftment occurs earlier. Further investigations in the future are required to determine the factors affecting the process of early engraftment. Abstract : After allogenic hematopoietic stem cell transplantation (HSCT), granulocyte colony stimulating factor (GCSF) is administrated to improve the neutrophil and platelet recovery. If the number of injected GCSF is <14 units until +11 day, the rate of early neutrophil engraftment will be three times better than the injected GCSF is ≥14 units.